Electron spin resonance analysis and interpretation - Rieger, Philip Henri, 1935- (Royal Society of Chemistry, 2007)
This volume describes in mathematical terms the extraction of useful information from ESR spectra as applied to paramagnetic organic, inorganic and organometalic molecules.
Keywords: Electron paramagnetic resonance.; elektronické knihy; electronic books